Potential Involvement of Complement Activation in Kidney Vascular Lesions of Arterionephrosclerosis - Chen, Xuejing; Wang, Yu; Yu, Xiaojuan; Wang, Suxia; Zhao, Minghui (Frontiers in Medicine, 2022)
Background Complement dysregulation has been implicated in the pathogenesis of malignant nephrosclerosis with typical pathological manifestation as thrombotic microangiopathy (TMA) in recent studies. The aim of the present study was to evaluate the potential role of complement activation in arterionephrosclerosis, the major pathological change in benign hypertensive nephrosclerosis. Methods Patients with biopsy-proven arterionephrosclerosis from 2010 to 2018 in our center were retrospectively enrolled in the present study. The clinical data were retrieved from the medical chart record. The pathological changes of renal biopsy were semiquantitatively evaluated. The ratio of inner-/outer-luminal diameter of the arterioles was calculated to evaluate the degree of arteriosclerosis. Immunohistochemical staining of CD34 and CD68 was adopted to evaluate peritubular capillary (PTC) density and macrophage infiltration, respectively. Complement components, including C3d, C4d, C1q and C5b-9, were detected by immunohistochemical staining in paraffin-embedded sections. IgM and albumin were detected by immunofluorescence staining in frozen renal tissues. Results Fifty-two patients were enrolled. The mean age was 45.0±12.7 years, with 39 (75%) males. The median duration of hypertension was 66 months (IQR: 24-138 months). A total of 950 arterioles were evaluated, with a mean ratio of the inner/outer luminal diameter of 0.43±0.05. The ratio of the inner-/outer-luminal diameter correlated with eGFR (r=0.341, p=0.013), sclerotic/ischemic glomerular lesions (r=-0.364, p=0.008) and PTC density (r=0.426, p=0.002). Seventy-four percent (703/950) of the evaluated arterioles had C3d deposition with various patterns and intensities. The percentage of C3d-positive arterioles ranged from 63.6% to 100.0% in each specimen. The ratio of the inner/outer luminal diameter of arterioles correlated with the intensity of C3d deposition (r=-0.174, p=0.001). Infiltration of macrophages was observed around C3d-positive arterioles. The percentage of C3d-positive arterioles was correlated with macrophage infiltration in each specimen (r=0.330, p=0.018). Occasional C4d-positive staining on arterioles was observed with no deposition of C1q or C5b-9 in arterionephrosclerosis specimens. Conclusion Our findings provide evidence for potential complement activation in the pathogenesis of vascular lesions in arterionephrosclerosis.